2019
DOI: 10.1002/art.40780
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Short‐, Mid‐, and Long‐Term Effects of Tofacitinib on Lymphocytes in Patients With Rheumatoid Arthritis

Abstract: Objective Tofacitinib is an oral JAK inhibitor for the treatment of rheumatoid arthritis (RA). Altered lymphocyte cell counts and a potential association with increased infection rates have been reported in RA patients treated with JAK inhibitors. This analysis was undertaken to evaluate the short‐, mid‐, and long‐term effects of tofacitinib on lymphocytes and infection rates in patients with RA. Methods In this post hoc analysis, absolute lymphocyte counts (ALCs) were obtained from phase III studies (12–24 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 39 publications
3
32
0
1
Order By: Relevance
“…Previous studies showed that tuberculosis infection caused by BCG vaccination usually occurs in immunodeficient children [7,8], especially for boys with low lymphocyte counts [9]. Due to the low lymphocyte counts, genetic analysis was performed, and the result of whole-exome sequencing confirmed the mutation in the IL2RG gene underlying X-SCID in the patient.…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies showed that tuberculosis infection caused by BCG vaccination usually occurs in immunodeficient children [7,8], especially for boys with low lymphocyte counts [9]. Due to the low lymphocyte counts, genetic analysis was performed, and the result of whole-exome sequencing confirmed the mutation in the IL2RG gene underlying X-SCID in the patient.…”
Section: Resultsmentioning
confidence: 97%
“…A pooled analysis of tofacitinib in patients with rheumatoid arthritis reported that patients with an ALC less than 500 cells/mm 3 had an increased risk of infection and identified trends towards an increased rate of herpes zoster and opportunistic infections with lower ALC values. 54 Dosing should be discontinued in patients with an ALC and ANC of less than 500 cells/mm 3 . Treatment should be interrupted in patients with a hemoglobin of less than 8 g/dL or a decrease of more than 2 g/dL.…”
Section: Discussionmentioning
confidence: 99%
“…Closeness centrality analysis assigned a high rank to Tofacitinib and Ruxolitinib, which are currently being assessed in clinical trials. Tofacitinib and Ruxolitinib exert immunomodulatory effects as Janus kinase inhibitors 20,21 . Thus, administration with these drugs may mitigate immune-mediated lung injury and reduce functional deterioration caused by an overamplified host inflammatory response.…”
Section: Resultsmentioning
confidence: 99%